2020
DOI: 10.1002/ldr.3699
|View full text |Cite
|
Sign up to set email alerts
|

Land degradation and climate change: Global impact on wheat yields

Abstract: This study aims at estimating the wheat yield response to future challenges (land degradation and climate change) through a statistical emulator. Data from Global Agro-ecological Zones on the overall wheat yields of 254 provinces for nine main wheat-producing countries and corresponding climate and land suitability information were collected to estimate the statistical relationship between regressors and wheat yields. Once the statistical emulator was calibrated, three scenarios were developed to predict, sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Lastly, the coefficient of land is detrimental to wheat yield as it can be observed that with 1% change in the land would negatively impact the wheat yield by 0.164%. Various reasons may lead to such situations, and supporting the estimation of the current study as land degradation is offsetting more than climate change (Raimondo et al, 2021). Further, a positive relationship can be seen between ownership of land and rice yield in India (Koirala, 2014) and land inequality suppressing the farmers to use resources and affecting rice productivity adversely (Prasanna et al, 2009).…”
Section: Insert [Table 9]supporting
confidence: 78%
“…Lastly, the coefficient of land is detrimental to wheat yield as it can be observed that with 1% change in the land would negatively impact the wheat yield by 0.164%. Various reasons may lead to such situations, and supporting the estimation of the current study as land degradation is offsetting more than climate change (Raimondo et al, 2021). Further, a positive relationship can be seen between ownership of land and rice yield in India (Koirala, 2014) and land inequality suppressing the farmers to use resources and affecting rice productivity adversely (Prasanna et al, 2009).…”
Section: Insert [Table 9]supporting
confidence: 78%
“…The crop yield risk was measured by multi-model ensemble (MME) simulation using global high spatial resolution (0.25°) climate forcing data. To enable such MME simulation, the development of emulators of global gridded crop models (GGCM) is required (Lobell and Burke 2010;Holzkämper et al 2012;Oyebamiji et al 2015;Raimondo et al 2020). The present results may provide crucial information for climate risk assessment and effective adaptations.…”
Section: Introductionmentioning
confidence: 96%
“…Generally, the imbalanced source-sink relationship deteriorates the wheat yield and quality by reducing root absorption capacity, declining photosynthetic activity, poor spike differentiation, and delayed grain filling under LTS (Li et al, 2014;Zhang et al, 2019;Kul et al, 2020). Soil degradation also greatly interferes with wheat productivity (Alewell et al, 2020;Raimondo et al, 2020). Phosphorus (P) is an essential nutrient for wheat growth and development, and about 40% agricultural lands are deficient in P worldwide (Lynch, 2011;Rafiullah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%